Hemodynamic effects of pulsatile unloading of left ventricular assist devices (LVAD) on intraventricular flow and ventricular stress. (16th April 2020) - Gu, Kaiyun; Guan, Zhiyuan; Chang, Yu; Gao, Bin; Ling, Yunpeng; Song, Zhiming; Wan, Feng
Abstract: The role of pulsatile unloading in hemodynamic changes in intraventricular flow and ventricular wall stress remains unknown. In this study, a finite element model of the left ventricle (LV) is proposed to calculate the mechanical response. The constitutive model of the LV is composed of a quasi-incompressible transversely isotropic model and an active contraction of the myocardium model. Pulsatile unloading is provided by the left ventricular assist device (LVAD), which is implanted between the aortic root and aortic arch. Support models (constant speed and co-pulse) were utilized to study the effect of pulsatile unloading on intraventricular flow and ventricular stress. The result indicates that the formation time of the vortex increases under pulsatile unloading. The area rate of high time-averaged wall shear stress (TAWSS) increased after pulsatile unloading. The area of the high oscillatory shear index (OSI) region (OSI > 0.375) was calculated for heart failure, constant speed, and co-pulse (9.9 cm 2, 9.6 cm 2, and 9.2 cm 2, respectively). The maximum value of the stress that reflects the level of stretch declined after pulsatile unloading (66.4 kPa, 30.9 kPa, and 21.3 kPa, respectively). Besides, pulsatile unloading impacts the maximum value of thickness at the ventricular wall (−0.75 mm, −1 mm, and −1.25 mm, respectively). The change ratios of the thickness are 10%, 14%, and 17%, respectively. In conclusion, pulsatile unloading contributes to the distribution of intraventricular flow and the formation time of the vortex. Co-pulse support significantly reduces the maximum value of the ventricular wall stress and the area of high stress on the ventricular wall.